Design and synthesis of a potent inhibitor of class 1 DYRK kinases as a suppressor of adipogenesis. Issue 15 (1st August 2015) - Masaki, So; Kii, Isao; Sumida, Yuto; Kato-Sumida, Tomoe; Ogawa, Yasushi; Ito, Nobutoshi; Nakamura, Mitsuhiro; Sonamoto, Rie; Kataoka, Naoyuki; Hosoya, Takamitsu; Hagiwara, Masatoshi
Graphical abstract: Abstract: Dysregulation of dual-specificity tyrosine-phosphorylation-regulated kinase 1A (DYRK1A) has been demonstrated in several pathological conditions, including Alzheimer's disease and cancer progression. It has been recently reported that a gain of function-mutation in the human DYRK1B gene exacerbates metabolic syndrome by enhancing obesity. In the previous study, we developed an inhibitor of DYRK family kinases (INDY) and demonstrated that INDY suppresses the pathological phenotypes induced by overexpression of DYRK1A or DYRK1B in cellular and animal models. In this study, we designed and synthesized a novel inhibitor of DYRK family kinases based on the crystal structure of the DYRK1A/INDY complex by replacing the phenol group of INDY with dibenzofuran to produce a derivative, named BINDY. This compound exhibited potent and selective inhibitory activity toward DYRK family kinases in an in vitro assay. Furthermore, treatment of 3T3-L1 pre-adipocytes with BINDY hampered adipogenesis by suppressing gene expression of the critical transcription factors PPARγ and C/EBPα. This study indicates the possibility of BINDY as a potential drug for metabolic syndrome.